Temporomandibular joint function 10-15 years after mandibular setback surgery and six weeks of intermaxillary fixation - Mohammedreza Sefidroodi; Ole Kristian Lobekk; Sigbjørn Løes; Elisabeth Schilbred Eriksen
Abstract Intermaxillary fixation (IMF) is a classic method for immobilization of the mandible after mandibular fractures and corrective surgery. However, it has been suggested that IMF may be a risk for developing temporomandibular joint (TMJ)-related symptoms, especially when applied for longer periods. Objective: To evaluate the clinical function of TMJs and masticatory muscles 10-15 years after mandibular setback surgery and subsequent six weeks of IMF. The patients' self-reported TMJ and masticatory muscle symptoms were also addressed. Methodology: Thirty-six patients (24 women and 12 men) treated with intraoral vertical ramus osteotomies and subsequent six weeks of IMF, underwent a clinical examination of TMJs and masticatory muscles 10-15 years after surgery and completed a five-item structured questionnaire reporting subjective TMJ-related symptoms. Mean age by the time of clinical examination was 34.1 years (range 27.2-59.8 years). The clinical outcome was registered according to the Helkimo clinical dysfunction index. Descriptive and bivariate statistics were performed and level of significance was set to 5%. Results: Mean maximum unassisted mouth opening 10-15 years after surgery was 50.1 mm, (range 38-70 mm, SE 1.2), statistically significantly greater in men compared to women (p=0.004). Mean Helkimo dysfunction group was 1.5 (range 1-3, SE 0.10). Eighty-one percent experienced pain on palpation in either the masseter muscle, temporal muscle or both, and 31% experienced pain when moving the mandible in one or more directions. Thirty-one percent reported pain from palpating the TMJs. In the questionnaire, none reported to have pain during chewing or mouth opening on a weekly or daily basis, but 22% reported difficulties with maximum opening of the mouth. Conclusion: Ten to fifteen years after mandibular setback surgery the patient's mandibular range of movement is good. Despite clinically recognizable symptoms, few patients reported having TMJ- or masticatory muscle-related symptoms in their daily life.